Factors involved in vulvar pain during sexual activity and persistence in sexual activity amidst pain - Carlotta Oesterling; Amelie Harder; Charmaine Borg; Peter de Jong (PLoS ONE, 2025)
Evidence suggests that women often endure pain during sexual activity, continue engaging in such activity despite experiencing pain, and tend to avoid communicating these painful experiences to their partners. The present study aims to shed light on psychosocial factors that may contribute to vulvar pain and the engagement in sexual activity despite pain, with a specific focus on the relevance of sexual self-esteem, the definition of sex (limited to penile-vaginal intercourse or inclusive of other intimate behaviours), sexual agency, and sexual motivation. A sample of N = 277 female students of a Dutch University was included. Participants were between 18 and 33 years old. The primary outcome measures were female sexual distress, sexual function, and vulvar pain. Engagement in sexual activity despite pain, pain communication, sexual agency, and relationship satisfaction were included as mediators. The majority of participants (80.0%) reported to experience pain at least sometimes, and 15.0% reported to experience pain more than half of the time. Engaging in penile-vaginal intercourse despite experiencing pain was common, with 42.0% of participants indicating to do so always or most of the time and 65.0% at least sometimes when experiencing pain. Of the affected women, 41.0% did not communicate pain to their partners. Low sexual self-esteem, a restrictive definition of sex, limited sexual agency, and low autonomous sexual motivation were all significantly related to at least one of the primary outcome variables. These associations were partly mediated by engagement in PVI despite pain, (no) pain communication, and (low) relationship satisfaction.